Artificial Bee Colony in the Hopfield Network for Maximum \(k\)-Satisfiability Problem (Journal of Informatics and Mathematical Sciences, 2016)
Artificial bee colony (ABC) is a relatively new swarm intelligence method that solve various type of optimization problems. This algorithm utilized the behavior of the actual bees to minimize or maximize the cost function of any combinatorial problems. The aim of this study is to introduce the hybridization of artificial bee colony algorithm with Hopfield network in doing Restricted MAX-kSAT. The performance of the proposed paradigm will be compared with conventional Hopfield network. The result obtained from computer simulation indicates the beneficial features of ABC towards Hopfield network in doing MAX-kSAT. The findings have led to a significant implication on the choice of determining an alternative method to do MAX-kSAT problem.
Keywords: Artificial bee colony; Hopfield neural network; Maximum k-Satisfiability